Neoadjuvant radiotherapy provided survival benefit compared to adjuvant radiotherapy for hepatocellular carcinoma. Issue 10 (5th February 2018) - Lin, Huapeng; Li, Xiaocheng; Liu, Ye; Hu, Yingchun
Abstract : Background: This study compared the impact of neoadjuvant radiotherapy (RT) and adjuvant RT on survival for patients with hepatocellular carcinoma (HCC). Methods: Patients with HCC were identified from the Surveillance, Epidemiology and End Results (SEER) database. The Kaplan–Meier method and multivariate Cox regression analysis were used to compare the impact of neoadjuvant RT on survival with adjuvant RT. Subsequently, a propensity score‐matched analysis was performed to confirm the result. Results: A total of 244 patients with HCC identified from the SEER database (2004–2014) received preoperative or post‐operative radiation. A total of 151 patients received post‐operative RT and 93 patients received preoperative RT. Preoperative RT had a clear superiority in terms of unadjusted overall survival and cancer‐specific survival ( P < 0.001 for log‐rank test). After adjusting for confounding variables, hazard ratios (HRs) for all‐cause (HR: 0.33; 95% CI: 0.19–0.53, P < 0.001) and cancer‐specific (HR: 0.32; 95% CI: 0.19–0.53, P < 0.001) mortality risks in preoperative RT group were significantly lower than that of post‐operative RT group. Subsequently, a propensity score‐matched analysis was performed to confirm this result. Further univariate and multivariate survival analyses revealed that there was a persistent superiority of overall survival and cancer‐specific survival in patients who received preoperative radiation than patients without RT. Conclusion: We found that neoadjuvant RT was associated with improved long‐term survival for patients with HCC versus adjuvant RT.